Mathematical Model Of Regulation Of Dynamic Processes In Systems With Distributed Parameters (On The Example Of Flooding In Oil Fields) - Suvonov Olim Omonovich (Genius Journals, 2025)
The paper considers an applied problem of regulating dynamic flooding processes in the development of oil fields. Mathematical models, computational algorithms, and the results of a computational experiment are presented.
Keywords: optimal control; regulation; dynamic process